O princípio da segurança jurídica e a superação do precedente judicial - Carreira, Guilherme Sarri (2013)
This paper aims to examine the issue of overcoming judicial precedents against the principle of legal certainty, that is, the focus of this dissertation is to understand the effect in cases where the court changes an already consolidated position. This perception should avoid the evils of the so called staggered or zigzag jurisprudence , a fact that has always troubled us. To this effect, we analyze in depth the principle of legal certainty, as well as all causes of insecurity. Among those, the legal one consists exactly in this change of jurisprudence. Furthermore, we made a thorough analysis of the theory of judicial precedents, covering all its nuances, both in common and in civil law. We thus concluded that in cases of overcoming judicial precedents, the rule should be the prospective effect except in cases of granting greater protection to fundamental rights